Bilateral Olecranon Tophaceous Gout Bursitis - Güzelali Özdemir; Alper Deveci; Kemal Andıç; Niyazi Erdem Yaşar (Case Reports in Medicine)
In this case, we present a patient with the diagnosis of bilateral olecranon tophaceous gout. After the surgical treatment, there was no limitation of range of motion or wound problem at 6th month control.